Uma arqueologia do conceito de langue no curso de linguística geral e no proposições para uma semiologia e uma linguística - Donatti, Silvério Guazzelli (Universidade Federal de São Carlos, 2018)
The present research will be based on the work of the Archeology of knowledge of Michel Foucault, an analysis of two saussurians discursive formations, with a view to the apprehension of the relations involving the concept of langue present in the works that compose our corpus, namely: the Course of General Linguistics, organized and edited by Charles Bally and Albert Sechehaye in France in 1916, and the Propositions for a Semiology and a Linguistics, a materialistic proposal articulated by Carlos Henrique de Escobar in Brazil in 1973. Our hypothesis was denied of a possible mutual re-elaboration between both discursive formations, through the concept of langue, due to the incompatibilities in the base of the discursive events that surround the concept.
An archeology of the concept of langue in the course of general linguistics and in the propositions for a semiology and a linguistics
Keywords: Langue; Saussure; Arqueologia do Saber; Formação Discursiva; Archeology of Knowledge; Discursive Formations; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA